022 Voxelwise analysis of cerebral diffusion tensor imaging in prion diseases. Issue 3 (9th February 2012) - Porter, M C; Hyare, H; De Vita, E; Thompson, A; Lukic, A; Yousry, T; Rudge, P; Mead, S; Collinge, J; Thornton, J
Abstract : The need to find a prion disease neuroimaging biomarker is important with the development of therapeutic agents. Diffusion tensor imaging (DTI) is an MRI sequence that can visualise white matter changes in the brain. Voxel-based analysis of DTI and voxel based morphometry (VBM) was performed on 17 asymptomatic prion protein gene mutation carriers, 14 symptomatic inherited prion disease patients, seven sporadic CJD patients (sCJD) and 24 healthy controls. There were significant differences found in grey matter voxels between the symptomatic and the control patients in the cortex bilaterally. In addition there was reduced fractional anisotropy in the corpus callosum, frontal white matter, internal capsule, optic radiation and cerebellum; these regions did not overlap with areas of brain atrophy. In the asymptomatic patients there were directional changes seen in keeping with the symptomatic patients, but due to the small patient number no statistically significant differences were found with VBM and voxel based analysis of DTI. In sCJD grey matter changes were found in the thalamus on VBM but voxel based analysis of DTI demonstrated change in the corpus callosum, thalamus and cerebellar white matter. These data show that voxel based analysis of DTI can detect significant microstructural white matter changes in the absence of its loss. DTI may prove to be a useful biomarker in prion disease.